Application of Lentivirus Vectors to Adult Neurogenesis and Manipulation of Neural Stem Cells - Imayoshi, Itaru; Yamada, Mayumi; Nagasaki, Shinji C.; Fukuda, Tomonori D.; Nagano, Ikumi; Toda, Tomohisa (Humana Press Inc., 2026)
Lentivirus vectors are capable of efficient gene transfer to nondividing cells, in addition to dividing cells. Therefore, lentivirus vectors can also be used for gene transfer into dormant stem cells in the postnatal and adult brains of experimental animals, many of which have ceased cell division. For example, it is known that neural stem cells (NSCs) are present around the lateral ventricle and in the dentate gyrus of the hippocampus in the postnatal and adult brain and continue to give rise to neuronsNeuron. However, the majority of these NSCs are considered to be quiescent, and lentivirus vectors are an important tool to enable gene transfer to dormant stem cells. Lentivirus vectors are also capable of multiple infection of the same cells, making them an important option for experiments requiring high gene expression levels. By selecting transduced cells after infection with high titer lentivirus vectors and repeating infection, genes that are difficult to express or gene sequences that require high copy number can be introduced into cells with high efficiency. In this chapter, we present examples of gene transfer to NSCs localized at the hippocampal dentate gyrus in mice using lentivirus vectors and establishment of stable transgenic NSC lines by multiple infections.
CRIS-Team Scopus Importer:2025-12-05
Keywords: bHLH transcription factor; Hippocampus; Lentivirus vector; Neural stem cells; Optogenetics; Quiescent cells